2018
DOI: 10.1002/htj.21345
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the convective heat transfer and flow behavior around two counter‐rotating side‐by‐side cylinders

Abstract: This study presents details of the heat and fluid flow around two counter-rotating cylinders. For this goal, three different nondimensional gap spaces such as G/D = 1.5, 2.0, and 3.0 are examined in the constant Reynolds number of 200 and Prandtl number of 7.0. In addition, computations are carried out at various nondimensional rotating speeds (R.S) in the range from 0 to 4. The obtained results are validated against the available data in the open literature for stationary cases.The results showed that the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Typical assumptions such as the laminar, incompressible flow of Newtonian fluid with constant properties are applied. [34][35][36][37] All the parameters in equations ( 1) to (3) are dimensionless. The scaling parameter for velocity u…”
Section: Numerical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Typical assumptions such as the laminar, incompressible flow of Newtonian fluid with constant properties are applied. [34][35][36][37] All the parameters in equations ( 1) to (3) are dimensionless. The scaling parameter for velocity u…”
Section: Numerical Analysismentioning
confidence: 99%
“…Typical assumptions such as the laminar, incompressible flow of Newtonian fluid with constant properties are applied. 3437 …”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the thermal features of the heat transfer between the cylinder and its cavity lie in accordance with the value of the Ra and cylinder location. Convection in two opposite rotating cylinders is analysed by Darvishyadegari and Hassanzadeh . Authors proposed that vortex shedding process and flow structure is heavily affected by the rotating speed of cylinders and gap spaces between them.…”
Section: Introductionmentioning
confidence: 99%
“…In another work by the same authors [29] regarding the heat and fluid flow around two co-rotating tandem cylinders, it has been demonstrated that a uniform Nusselt number distribution can be observed on both cylinders regardless of the gap space between them. Analysis of convective heat transfer and flow nature around two counter-rotating side-by-side cylinders is the subject of a research work performed by Darvishyadegari and Hassanzadeh [30]. They examined several gap spaces and rotating speeds at constant Reynolds number of 200.…”
Section: Introductionmentioning
confidence: 99%